2018
DOI: 10.1080/14786419.2018.1516664
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant activity of Rhaponticum acaule (L.) DC

Abstract: Rhaponticum acaule (L.) DC. is a medicinal plant commonly used for the treatment of some illnesses such as gastrointestinal infections. In this work, we report the composition of different parts of this plant on phenolic compounds, their quantification, and antioxidant activity. The obtained results reported that methanolic extracts of the three parts studied revealed high phenolic contents. For flavonoid contents, the highest contents were reported in organic extracts of leaf part. In addition, results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The DPPH scavenging capacity test and the FRAP test, both of which were used to evaluate the antioxidant activity of the root extract, found that the methanolic extract of the root had the maximum activity. Five phenolic acids (chlorogenic, caffeic, ferulic, syringic, and sinapic), one flavanone (naringenin), one flavonol (rutin), and vanillin were identified through the RP-HPLC-PDA analysis [94].…”
Section: Rhaponticum Acaule Essential Oilmentioning
confidence: 99%
“…The DPPH scavenging capacity test and the FRAP test, both of which were used to evaluate the antioxidant activity of the root extract, found that the methanolic extract of the root had the maximum activity. Five phenolic acids (chlorogenic, caffeic, ferulic, syringic, and sinapic), one flavanone (naringenin), one flavonol (rutin), and vanillin were identified through the RP-HPLC-PDA analysis [94].…”
Section: Rhaponticum Acaule Essential Oilmentioning
confidence: 99%